Spontaneous and antigen-induced production of HIV-inhibitory β-chemokines are associated with AIDS-free status - Garzino-Demo, Alfredo (The National Academy of Sciences, 1999)
The β-chemokines RANTES, macrophage inflammatory protein (MIP)-1α, and MIP-1β suppress infection by macrophage-tropic strains of HIV and simian immunodeficiency virus (SIV) by binding and down-regulating the viral coreceptor, CCR5. Accordingly, we have examined whether higher levels of CCR5 ligands are associated with a more favorable clinical status in AIDS. A cross-sectional study of 100 subjects enrolled in the Multicenter AIDS Cohort Study at the Baltimore site was conducted to measure chemokine production and lymphocyte proliferation by peripheral blood mononuclear cells (PBMC). Statistical analyses of the data revealed that the production of HIV-suppressive β-chemokines by HIV antigen-stimulated PBMC was significantly higher in HIV-positive subjects without AIDS compared with subjects with clinical AIDS. Increased chemokine production was also correlated with higher proliferative responses to HIV antigens. Both parameters were significantly lower in the AIDS versus non-AIDS group. Notably, significantly higher levels of MIP-1α were also observed with unstimulated PBMC from seronegative subjects at risk for HIV infection released as compared with seropositive and non-Multicenter AIDS Cohort Study seronegative subjects. The association of chemokine production with antigen-induced proliferative responses, more favorable clinical status in HIV infection, as well as with an uninfected status in subjects at risk for infection suggests a positive role for these molecules in controlling the natural course of HIV infection.